Lifecycle-oriented framing of value at the front end of infrastructure projects. Issue 3 (2nd September 2019) - Martinsuo, Miia Maarit; Vuorinen, Lauri; Killen, Catherine
Abstract : Purpose: Infrastructure projects are expected to deliver value to their stakeholders long after completion. Project value is multi-dimensional and subjective and evolves over the project lifecycle. How stakeholders frame the expected value is central to the public debate about proposed infrastructure projects and influences the financing decisions; however, this framing is inadequately understood. The purpose of this paper is to develop new knowledge for shaping infrastructure projects by identifying the ways in which stakeholders frame project value at the project front end. Design/methodology/approach: Three transport infrastructure projects are compared in a qualitative, document-based study. The authors map the dimensions of value at the project front end and identify stakeholders' approaches to lifecycle-oriented framing of value. Findings: Financial, social and comparative values are dominant in the project front end. The authors frame value into positive and negative dimensions and identify four themes in the lifecycle-oriented framing of value, including uncertainties, timing of cost and benefit realization, project relations and external sponsorship. Research limitations/implications: The research is limited through the focus on transport infrastructure projects and project front end only, the selection of cases from a single country and the use of document-based data. The systematic analysis approach has yielded novel analytical frameworks that will be useful for further research. Practical implications: This study identifies value dimensions that are specific to transport infrastructure projects and proposes a framework to assist stakeholders and project managers to better assess and negotiate value when designing their projects. Originality/value: Regional and comparative values are revealed as novel aspects of value specific to infrastructure projects. The alternative lifecycle-oriented frames offer a new way to understand and structure the co-creation of value and shape negotiation for investment decisions in the project. A portfolio perspective to investment decision making is proposed.